Abnormal neuronal response to rectal and anal stimuli in patients treated with primary radiotherapy for anal cancer. Issue 2 (August 2018) - Haas, Susanne; Faaborg, Pia; Gram, Mikkel; Lundby, Lilli; Brock, Christina; Drewes, Anbjørn M.; Laurberg, Søren; Krogh, Klaus; Christensen, Peter
Abstract: Introduction: Sphincter-sparing radiotherapy or chemoradiation (RT/CRT) have become the standard treatments for most patients with anal cancer. Unfortunately, long-term survivors often suffer from severe bowel symptoms indicating sensory dysfunction. The aim of the present study was to characterize the sensory pathways of the brain–gut axis after radiotherapy for anal cancer. Method: Cortical evoked potentials (CEPs) were recorded during repeated, rapid balloon distensions of the rectum and anal canal in 13 patients with anal cancer treated with radiotherapy or chemoradiation and in 17 healthy volunteers. Latencies and amplitudes of rectal CEPs were compared between the groups. CEPs from both rectal and anal distensions were examined using single sweep spectral band analysis to determine the relative amplitude of five spectral bands as a proxy of neuronal processing. Results: Groups were comparable by age (62.4 ± 7.8 vs 58.9 ± 8.9, p < 0.32) and gender. Patients had a mean Wexner fecal incontinence score of 5.5 (±3.8) and median LARS Score of 29 (0–39). Rectal CEP latencies were prolonged in patients ( F = 11.7; p < 0.001), whereas amplitudes were similar ( F = 0.003; p = 0.96). Spectral analysis of CEPs from rectal distensions showed significant differences between groups in theta (4–8 Hz), alpha (8–12 Hz), beta (12–32 Hz) and gamma (32–70 Hz) bands (all p < 0.001) and CEPs from anal distensions showed significant differences in the alpha, beta and gamma bands (all p ≤ 0.002). Conclusion: Patients treated with RT/CRT for anal cancer have impaired ano-rectal sensory pathways and abnormal cortical processing. This may play a central role for the pathogenesis of late proctopathy.